Directional Phosphorylation and Nuclear Transport of the Splicing Factor SRSF1 Is Regulated by an RNA Recognition Motif. Issue 11 (5th June 2016) - Serrano, Pedro; Aubol, Brandon E.; Keshwani, Malik M.; Forli, Stefano; Ma, Chen-Ting; Dutta, Samit K.; Geralt, Michael; Wüthrich, Kurt; Adams, Joseph A.
Abstract: Multisite phosphorylation is required for the biological function of serine–arginine (SR) proteins, a family of essential regulators of mRNA splicing. These modifications are catalyzed by serine–arginine protein kinases (SRPKs) that phosphorylate numerous serines in arginine–serine-rich (RS) domains of SR proteins using a directional, C-to-N-terminal mechanism. The present studies explore how SRPKs govern this highly biased phosphorylation reaction and investigate biological roles of the observed directional phosphorylation mechanism. Using NMR spectroscopy with two separately expressed domains of SRSF1, we showed that several residues in the RNA-binding motif 2 interact with the N-terminal region of the RS domain (RS1). These contacts provide a structural framework that balances the activities of SRPK1 and the protein phosphatase PP1, thereby regulating the phosphoryl content of the RS domain. Disruption of the implicated intramolecular RNA-binding motif 2–RS domain interaction impairs both the directional phosphorylation mechanism and the nuclear translocation of SRSF1 demonstrating that the intrinsic phosphorylation bias is obligatory for SR protein biological function. Graphical abstract: Highlights: SRPK1 catalyzes multisite phosphorylation of SRSF1 using a directional mechanism. Several charged residues in RRM2 interact with RS domain in SRSF1. RRM2–RS domain interactions control directional phosphorylation. Directional phosphorylation regulates subcellular localization of SRSF1. Phosphorylation mechanism is tied to biological function of an SR protein.